Relações entre preferências térmicas humanas no interior de edificações e as temperaturas externas: um estudo sobre o método adotado na norma AHSRAE 55-2004 - Gomes, Adriana Dias (2007)
Thermal comfort is specifically related to thermal behavior in response to both indoor and outdoor air temperature. Human thermal acceptability to climate changes and its effects depend on several aspects. It relies not only on local climatic conditions, but also on personal traits which can interfere seriously with thermal preferences as well as with someone s mental and physical performance. The combination of these factors determines the human thermal acceptability and the satisfaction degree in relation to a specific environment. The more those conditions vary, the higher the percentage of dissatisfied people with an environment is, due to personal requirements of each person. Thus, meeting those expectations of thermal comfort, considering people s needs and limitations, has been an important subject of studies in this field highlighting its importance when planning, designing, and constructing a building. Therefore, human thermal preferences and thermal sensations to hot and cold environments are essential information to various activity sectors because comfort and human performances depend directly on environmental thermal conditions. Since architecture, mainly buildings, is intended for humans, it can be said that it should satisfy its occupants, regarding local climate conditions. In order to have this, it s necessary to determine the comfort temperatures in which people develop better their work activities, optimizing their mental, physical, and intellectual well being. This research consists of a theoretical analytical study of the international large database, compiled by ASHRAE (1997), combining climate conditions with human thermal preferences and sensations. The methodology used by Richard De Dear (1997) in the RP-884 ASHRAE s project was the probit procedure using SAS software, release 8 (SAS Institute, Cary, NC, USA, 1999) to the optimum temperatures obtained, and linear regression to the acceptable comfort limits of the population studied. The comfort limits obtained demonstrate the ratio between occupants comfort temperature and the outdoor temperature, featuring fluctuations of 80% to 90% of thermal acceptability in well-ventilated buildings. The aim of this study is to interpret the method adopted by Richard De Dear (1997) and apply it to the data resulting from the large ASHRAE (2004) Database to understand how the comfort temperatures (optimum temperatures) and the thermal acceptability were obtained for a group of people under predetermined indoor thermal conditions in well- ventilated buildings. The Probit analysis indicates the optimum temperature is 25ºC approximated, exactly 0,5 probability responses, that is, 50% interviewees. In the face the obtained results, it s succeeded the Probit analysis applicability has a great efficacy method to binary variable probability study and determination, which points out two interesting situations to research